IMPLEMENTATION OF GAME-DESIGN CONCEPTS DURING DEVELOPMENT OF THE GAME PROJECT «MAVKA» IN THE CONDITIONS OF MODERN REQUESTS - Колісник, О. В.; Гула, Є. П. (Art and Design, 2019)
The purpose of the study is to identify the features of creating a competitive game-design and its implementation in the game project "Mavka", adapted to the modern needs of the target audience, both from the standpoint of artistic and expressive means and technological limitations, and stylistic features caused by the genre of the project. Methodological basis of the study is a comparative method of analysis of successfully implemented game projects, which allowed to reveal the essential characteristics of the latter. The analysis of the functioning of avatars in game design was made possible by the modeling method. Also, the method of system analysis of publications and sociological methods were used, which allow to determine the basic patterns of the development of game content design, its direct influence on the perception of the target audience of the project, the needs and expectations of society. The results of this scientific study have a theoretical significance, which is to determine the influence of the characteristics of the character, his appearance, biography, attributes and game behavior to increase the degree of empathy experienced by the user in relation to the game character within the gameplay, given the modern socio-cultural realities reflected in the game. Also, the article studies the artistic and aesthetic qualities of the project and its general attractiveness for the target audience. The analysis of the main principles of the creation and development of game characters has been carried out, and the main points have been defined in terms of players' needs and game-design abilities. The results provide an opportunity for a deeper understanding of the use of these developments to optimize the process of finding appropriate artistic and expressive means at the development stage of the visual component of the game project, the development domestic video games, as well as mobile games, whose aesthetic, technological and consumer properties will meet the expectations of the target audience and provide decent competition to foreign counterparts.